2021
DOI: 10.1186/s13293-021-00367-2
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone: sex-dependent role in nervous system regulation and disease

Abstract: Thyroid hormone (TH) regulates many functions including metabolism, cell differentiation, and nervous system development. Alteration of thyroid hormone level in the body can lead to nervous system-related problems linked to cognition, visual attention, visual processing, motor skills, language, and memory skills. TH has also been associated with neuropsychiatric disorders including schizophrenia, bipolar disorder, anxiety, and depression. Males and females display sex-specific differences in neuronal signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 147 publications
0
36
0
2
Order By: Relevance
“…Thyroid deficiency during development affects the adequate development of brain which, depending on the stage of development, may induce several diseases as for example affect neural circuitry and cause autism observed more in boys. Neuropsychiatric disorders that are related to thyroid disfunction (more frequently affected in women) coincide with their higher incidence, for example, TH or TSH serum levels associate with Alzheimer disease in women ( 85 ). Subclinical hypothyroidism has been related with psychiatric disorders such as anxiety and depression ( 85 ).…”
Section: Sex Dimorphism Of Hpt Axis Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid deficiency during development affects the adequate development of brain which, depending on the stage of development, may induce several diseases as for example affect neural circuitry and cause autism observed more in boys. Neuropsychiatric disorders that are related to thyroid disfunction (more frequently affected in women) coincide with their higher incidence, for example, TH or TSH serum levels associate with Alzheimer disease in women ( 85 ). Subclinical hypothyroidism has been related with psychiatric disorders such as anxiety and depression ( 85 ).…”
Section: Sex Dimorphism Of Hpt Axis Activitymentioning
confidence: 99%
“…Neuropsychiatric disorders that are related to thyroid disfunction (more frequently affected in women) coincide with their higher incidence, for example, TH or TSH serum levels associate with Alzheimer disease in women ( 85 ). Subclinical hypothyroidism has been related with psychiatric disorders such as anxiety and depression ( 85 ). Few studies have associated sex differences in depressive patients with subclinical hypothyroidism; however, a recent study reports its prevalence in women with depression being approximately two times higher than in men ( 86 ).…”
Section: Sex Dimorphism Of Hpt Axis Activitymentioning
confidence: 99%
“…In fact, Weng et al (2017) reported similar results to this study, where MEHP was positively associated with FT4 in girls, but was not associated with T3 or T4. Disrupted thyroid function appears to be more prevalent in women compared to men [ 61 ], potentially related to the sex-specific regulation of thyroid hormones in the brain [ 62 ]. Still, significant associations between MEHP and FT4 have been demonstrated in adult male humans [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…SBGN has been widely used in biological system networks and provides a new method for the analysis and visualization of biological networks [73][74][75][76]. For example, the network diagram of metabolic pathways meeting the SBGN standard [77,78] and the molecular interaction diagram [79,80] have been constructed. In addition, the metabolic pathways in the KEGG database can be automatically converted into the SBGN format for visualization, while preserving as much as possible, the layout of important elements that may change as a result of model conversion [81].…”
Section: Systems Biology Graphical Notation (Sbgn)mentioning
confidence: 99%